PERANCANGAN APLIKASI E-MARKETING MENGGUNAKAN RESPONSIVE WEB DESIGN - Rio Agustian (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2021)
E-marketing is part of e-commerce which is a trading system through the internet, where the internet will continue to provide an up to date nature, so the company can provide product information services offered clearly and easily. This will have a good impact on the progress of the company if this system can be run properly. E-marketing is widely done to improve the company's brand image because it makes the company always remembered by its customers. E-marketing provides more convenience and benefits for the company, customers and business partners of the company. Seeing marketing media that are still conventional, it is built online responsive web design applications as a support for marketing media by using prototype methods. The purpose of this research is to analyze the strategy and design of e-marketing websites that are in accordance with the company and can meet customer needs, as a support for marketing media and make it easier for customers to obtain information about existing products. The conclusion is that companies should use the internet as their marketing medium by creating a company website, so that the products and information offered can be easily and quickly obtained by the public